PERTANGGUNGJAWABAN MARKETPLACE ONLINE DALAMPERLINDUNGAN DATA PRIBADI PELANGGAN BERDASARKANPERATURAN PERUNDANG-PERUNDANGAN DI INDONESIA - Muhammad Yaafi Al Ghazali (2022)
The thesis with the title Online Marketplace Accountability in The Protection of Customer Personal Data Based on Legislation in Indonesia, contains about, First about how the legal protection system for personal data in Indonesia, and Secondly how is the legal liability for personal data registered in the online marketplace in Indonesia The results of this study show that the importance of legal protection in Indonesia regarding personal data protection is the obligation of the organizer's marketplace as a form of protection and responsibility for consumers' data. As stated in Law No. 5 of 1999 concerning Consumer Protection. However, there are still frequent cases of personal data theft in Indonesia caused by the weak protection system in the system of each marketplace.